DESAIN MEDIA PEMBELAJARAN INTERAKTIF PENGENALAN TATA SURYA BAGI SISWA-SISWI SEKOLAH DASAR (STUDI KASUS: SD NEGERI 3 REJOSARI KOTABUMI) - Ade Moussadecq; Muhammad Redintan Justin; Dika Tondo Widakdo (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2025)
The use of interactive media can also increase student activity in learning and mastery of ideas so that the learning experience received by students becomes more varied and not monotonous. The research method used is the Qualitative Descriptive method. The purpose of this study is to reveal events or facts, circumstances, phenomena, variables, and conditions that occur during the research by explaining what happened. This study took a case study at SD Negeri 3 Rejosari, North Lampung Regency according to the needs of the research partners. The purpose of this study is to create interactive learning media for students to introduce the solar system.